Practical therapeutic approach in the management of diabetes mellitus secondary to Cushing’s syndrome, acromegaly and neuroendocrine tumours - Guarnotta, Valentina; Emanuele, Fabrizio; Salzillo, Riccardo; Bonsangue, Maria; Amato, Carlotta; Mineo, Mariagrazia Irene; Giordano, Carla (Frontiers in Endocrinology, 2023)
Cushing’s syndrome, acromegaly and neuroendocrine disorders are characterized by an excess of counterregulatory hormones, able to induce insulin resistance and glucose metabolism disorders at variable degrees and requiring immediate treatment, until patients are ready to undergo surgery. This review focuses on the management of diabetes mellitus in endocrine disorders related to an excess of counterregulatory hormones. Currently, the landscape of approved agents for treatment of diabetes is dynamic and is mainly patient-centred and not glycaemia-centred. In addition, personalized medicine is more and more required to provide a precise approach to the patient’s disease. For this reason, we aimed to define a practical therapeutic algorithm for management of diabetes mellitus in patients with glucagonoma, pheochromocytoma, Cushing’s syndrome and acromegaly, based on our practical experience and on the physiopathology of the specific endocrine disease taken into account. This document is addressed to all specialists who approach patients with diabetes mellitus secondary to endocrine disorders characterized by an excess of counterregulatory hormones, in order to take better care of these patients. Care and control of diabetes mellitus should be one of the primary goals in patients with an excess of counterregulatory hormones requiring immediate and aggressive treatment.